93Nb NMR Study of (K, Na)NbO3-Doped SiO2–Na2O–Al2O3 Glasses - Otsuka, Takahito; Cicconi, Maria Rita; Dobesh, David; Schroeder, Barbara; Hayakawa, Tomokatsu (physica status solidi (b), 2022)
Aluminosilicate glasses containing octahedral NbO6 units are developed for future applications as optical materials. Soda-aluminosilicate glasses doped with Nb-based alkaline perovskite crystals (K0.5Na0.5NbO3 [KNN]) at different doping levels (2–30 mol%) are studied by 93Nb nuclear magnetic resonance (NMR) spectroscopy. The Al2O3 concentration in the starting soda-aluminosilicate glass matrix is varied from 5 to 17 mol% to investigate the influence of the composition of local Nb structures with 4–5, 6, and 7–8 fold-oxygen coordination on the optical properties of the glasses. The chemical shifts are analyzed by comparison with the 93Nb NMR data of reference crystals, including KNN, to determine the feasibility of producing more NbO6 octahedra in the aluminosilicate glasses, where these octahedra are expected to promote the development of optically active Nb-glass-ceramics. The data show that both glass polymerization and KNN content influence the Nb local environment. Therefore, an appropriate amount of Al2O3 combined with an adequate doping level of the KNN perovskite is required to achieve the desired optical features. Contrary to expectations, a higher KNN doping level is achieved with the starting depolymerized soda-aluminosilicate glass containing 5 mol% Al2O3, leading to perovskite-like structures of NbO6 octahedra in the resultant glass system.
CRIS-Team Scopus Importer:2022-06-03
Keywords: aluminosilicate glasses; glass-ceramics; local structure analysis; Nb NMR; NbO; nuclear magnetic resonance; perovskites